Harmonic Distortion Analysis of an eGPU-Fed Aircraft EPDS with Phase-Shifted Carrier PWM - Peng Q.; Sun J.; Yang J.; Buticchi G.; Tan N.M.L.; Guenter S.; Wheeler P. (Institute of Electrical and Electronics Engineers Inc., 2025)
The integration of power electronics devices into on-board electrical power distribution systems (EPDS) has steadily increased due to the trend toward more electric aircraft (MEA) and all electric aircraft (AEA). Digital control and pulse width modulation (PWM) of these devices give rise to the electrical harmonics, which have been extensively discussed for utility grids. However, the variable fundamental frequency and relatively lower switching-to-fundamental (S2F) frequency ratio in the EPDS result in more severe harmonic distortion and coupling between different subsystems. Onboard power electronic converters (PECs) exhibit greater transparency in compacted environments compared to utility power systems. Therefore, their relative PWM phase-shifted carrier (PSC) angles can be harnessed to cancel switching harmonics. In this work, a 3-bus system with an electric ground power unit (eGPU) converter and two active front end (AFE) converters is used to restore the situation of ground powering of an aircraft. The effect of PSC angles of the PECs on the system harmonics distortion is studied with both balanced and unbalanced load situation. On this basis, an online total harmonic distortion (THD) monitor unit is proposed which could calculate the real-time THD level of the EPDS ac bus within one fundamental period. The accuracy of the proposed THD monitor is verified by PLECS simulation. ? 2024 IEEE.